Analisis Ketidaksesuaian Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di Isntitusi Pendidikan X Berdasarkan Hasil Audit SMK3 - Dwi Retno Ayunita; Bima Kurniawan; Baju Widjasena (Jurnal Riset Kesehatan Masyarakat, 2021)
Educational institutions are workplaces that can’t be separated from the risk of harm due to activities carried out by lecturers, employees, and / or laboratory officers in it. Occupational safety and health are implemented with the aim of reducing the risk of harm and increasing the productivity of teaching and learning activities. Therefore, this study aimed to analyze the discrepancy in the application of occupational safety and health management system (SMK3) based on the results of SMK3 audits in educational institutions X. This research was a type of qualitative research with analytical observational design that used an in-depth interview approach. The method of data retrieval was conducted through in-depth interviews with 4 informants as well as using secondary data. The results showed that the level of application of SMK3 in educational institutions X has been obtaining of gold certificate of SMK3 audit results in accordance with PP 50 of 2012 in the initial level category. While some of the things that caused the finding in clauses 1.2.2, 1.2.5, and 1.4.3 which were minor categories because educational institution X has not conducted training and certification for the person in charge of the designated K3 experts and also the designated emergency officers, as well as the lack of communication with the relevant agencies related to the P2K3 enforcement decree. Overall, the cause of the findings were due to workplace inconsistencies in fulfilling the implementation of SMK3. Therefore, awareness is needed related to K3’s commitment to top management so that the existing regulations in the workplace support the fulfillment of K3 regulations.